Synthesis, characterization and biological studies of S-4-methylbenzyl-β-N-(2-furylmethylene)dithiocarbazate (S4MFuH) its Zn2+, Cu2+, Cd2+ and Ni2+ complexes - Md Yusof, Enis Nadia; Ravoof, Thahira B. S. A.; Jamsari, Junita; Tiekink, Edward R. T.; Veerakumarasivam, Abhimanyu; Crouse, K. A.; M. Tahir, M. Ibrahim; Ahmad, Haslina (Elsevier BV, 2015)
S-4-methylbenzyl-β-N-(2-furylmethylene)dithiocarbazate (S4MFuH, 1) derived from the condensation reaction of furaldehyde (Fu) with S-4-methylbenzyldithiocarbazate (S4MBDTC) has been complexed with transition metal acetates to give Zn(S4MFu)2 (2), Cd(S4MFu)2 (3), Cu(S4MFu)2 (4) and Ni(S4MFu)2 (5). It is evident from the shift in ν(CN) and ν(NN) in the IR spectra of the complexes that deprotonated 1 acts as a bidentate ligand coordinating through the azomethine nitrogen and thiolato sulfur atoms. This was confirmed by single crystal X-ray diffractometry. The U-shaped dithiocarbazate 1 exists in the E configuration with the thione bond anti to the azo bond. A change in conformation is noted in the transition metal complexes resulting from deprotonation and NS-chelation. 2 and 3 display a distorted tetrahedral geometry with the major cause of the distortion being two close intramolecular M…O interactions. Binding interaction studies with calf thymus DNA demonstrated that 4 also had the strongest DNA binding affinity (Kb=2.85×104M−1) among all compounds prepared in this work. The Cu(II) complex, 4, was also moderately active against estrogen receptor-positive breast cancer cells, MCF-7 (IC50=3.02μM) while the remainder were inactive against MCF-7 and all showed no activity towards receptor negative breast cancer cells, MDA-MB-231.